1995
DOI: 10.1051/rnd:19950406
|View full text |Cite
|
Sign up to set email alerts
|

Effet de la progestérone sur le taux d'ovulation et la durée du cycle ovarien induits par effet mâle chez la brebis Barbarine et la chèvre locale tunisienne

Abstract: (May). In both experiments, half of the females received 20 mg of progesterone intramuscularly just before male introduction (day 0). Blood samples were taken at 4 h intervals from the time of introduction of the ram, for the determination of the time of the preovulatory LH surge in response to the 'ram effect' (Exp 1) and once a day from days 1 to 8 to determine plasmatic progesterone concentrations (Exp 1, Exp 2). The ovulation rate was determined by coelioscopy at days 4 and 9, and c!strus behaviour was mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
1
8
0
2
Order By: Relevance
“…However, in sheep and cattle, the intra-uterine administration of indomethacin prevents luteal regression (Lewis and Warren, 1977) and decreases PGFM in the plasma (Troxel and Kesler, 1984 (Southee et al, 1988) and at different moments after ovulation induction (Sankot and Murdoch, 1991 (Bensadoun and Reid, 1962). However, this is unlikely as when one administers intramuscularly 20 mg progesterone to hysterectomized ewes, the elimination of the hormone is slower (4 days, fig 3c) than in intact ewes (1 day, Lassoued et al, 1995 (Hunter et al, 1989). Progestagen treatment inhibits the establishment of oxytocin receptors and the release of prostaglandins in response to oxytocin administration (Vallet et al, 1990 (Rubianes et al, 1996) and probably reduces the increase in E2 secretion observed by Mattner and Braden (1972).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in sheep and cattle, the intra-uterine administration of indomethacin prevents luteal regression (Lewis and Warren, 1977) and decreases PGFM in the plasma (Troxel and Kesler, 1984 (Southee et al, 1988) and at different moments after ovulation induction (Sankot and Murdoch, 1991 (Bensadoun and Reid, 1962). However, this is unlikely as when one administers intramuscularly 20 mg progesterone to hysterectomized ewes, the elimination of the hormone is slower (4 days, fig 3c) than in intact ewes (1 day, Lassoued et al, 1995 (Hunter et al, 1989). Progestagen treatment inhibits the establishment of oxytocin receptors and the release of prostaglandins in response to oxytocin administration (Vallet et al, 1990 (Rubianes et al, 1996) and probably reduces the increase in E2 secretion observed by Mattner and Braden (1972).…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, the length of these cycles is less than 7 days (Oldham, 1980;Knight et al, 1981;Chemineau, 1983;Southee et al, 1988; Lassoued and Khaldi, 1993;Lassoued et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This provokes an important delay in the post-introduction events: LH surge and subsequent ovulations are delayed from 24 to 72 h, depending on the experiments [5,17,56,57]. This was also demonstrated in goats [58,59]. The concomitant suppression of short-lifespan CL and of enlargement of the interval, introduction of male-LH preovulatory surge, led to the proposition that the existence of these short-lifespan CL is due to an insufficient follicle maturation before ovulation [57].…”
Section: How Exogenous P4 Acts To Completely Suppress Short Cycles? Imentioning
confidence: 97%
“…Furthermore, short ovarian cycles result in scattered lambing because estrouses occur 18-21 and 24-27 days after introduction of rams. A pretreatment with 20 mg of progesterone (P4) on the day of ram introduction or 3 d before prevents short cycles, so that the first silent ovulation is followed by a normal cycle, with a single peak of estrus 18-21 days after the introduction of rams [6][7][8][9][10]. Estrus behaviour occurs at the first induced ovulation if ewes are treated with progestagen, such as fluorogestone acetate (FGA), using subcutaneous implants or intravaginal sponges [6,11].…”
mentioning
confidence: 99%